La Gastronomie, the fourth canto - Berchoux, Joseph (Petits Propos Culinaires, 2005)
Readers will recall that we are reprinting this poem in four parts, the first of which (with an exhortation by Peter Cooke) was in PPC 75. Here is the fourth and final canto, together with a letter to the author and his reply. The text which I have followed is that of the fifth edition, the first having appeared in 1801.